Asynchronous Bilateral Achilles Tendon Rupture with Selective Androgen Receptor Modulators: A Case Report. Issue 2 (April 2021) - Gould, Heath P.; Hawken, Jessica B.; Duvall, Grant T.; Hammond, Jason W.
Abstract : Case: A 36-year-old male competitive powerlifter sustained asynchronous bilateral Achilles tendon ruptures after using 2 types of selective androgen receptor modulators (SARMs). Both tendon ruptures occurred near the myotendinous junction and were treated with open surgical repair and an initial period of immobilization followed by progressive weightbearing and rehabilitation; no postoperative complications were observed. Conclusion: Previous studies have reported that anabolic androgenic steroids have a deleterious impact on tendon structure and function. This case suggests that SARM compounds may also predispose users to Achilles tendon rupture.